Genetic variation affects binge feeding behavior in female inbred mouse strains - Brandon A. Newmyer (Nature Portfolio, 2019)
Abstract Identifying genetic variants that regulate binge eating (BE) is critical for understanding the factors that control this behavior and for the development of pharmacological treatment strategies. Although several studies have revealed specific genes capable of affecting BE behavior, less is known about how genetic variation modulates BE. Thus, through a paradigm that promoted binge-like food intake through intermittent access to high calorie diet (HCD), we quantified food-intake in four inbred mouse strains: C57Bl/6J (B6), NOD/LtJ (NOD), 129S1/SvlmJ (S1), and A/J (AJ). We report that genetic variation likely influences the chronic regulation of food intake and the binge-like consumption of a palatable HCD. AJ mice consumed more of both standard chow and HCD than the other three strains tested when both diets were available ad libitum, while S1 mice consumed significantly less HCD than other strains during intermittent HCD access. Behavioral differences were also associated with differential changes in c-Fos immunohistochemistry in brain regions traditionally associated with appetite regulation. Our results identify 129S1/SvlmJ as a strain that exhibits low levels of binge feeding behavior and suggests that this strain could be useful in the investigation of the influence of genetic variation in the control of binge food intake.